The business of being born - Epstein, Abby; Lake, Ricki; New Line Home Entertainment (Firm) ([Burbank, CA] : New Line Home Entertainment, 2008)
"Inspired by their own unique birth experiences, producer Ricki Lake and director Abby Epstein team up to provide a nation of mothers-to-be with insight into the process of childbirth and the various options available when preparing for this special event. From pregnancy to the miraculous moment of birth, an informative celebration of the road to motherhood."--Container.
Originally released in 2007.
Documentary.
Bonus features: Ricki and Abby behind the scenes.
Director of photography, Paulo Netto ; editor, Madeleine Gavin ; music, Jason Moss ; executive producer, Ricki Lake.
Ricki Lake, Abby Epstein.
Not rated.
Keywords: Parturition -- United States; Midwifery -- United States; Pregnancy Outcome -- United States; Pregnant Women -- psychology -- United States